Bioethical Principlism in the Humanization of Childbirth Assistance - Ainoa Biurrun Garrido; Carme Perelló Íñiguez; Bárbara Vidal Tegedor (Revista Iberoamericana de Bioética, 2018)
The four principles of bioethics proposed by Beauchamp and Childress are commonly used to solve ethical issues in health sciences. This article suggests its application in the field of humanized attention to childbirth. Specifically, an analysis from a critical and contextualized perspective of principialism is proposed, considering the limitations of the original theory.